2022
DOI: 10.1038/s41598-022-05181-3
|View full text |Cite
|
Sign up to set email alerts
|

A new platform for ultra-high dose rate radiobiological research using the BELLA PW laser proton beamline

Abstract: Radiotherapy is the current standard of care for more than 50% of all cancer patients. Improvements in radiotherapy (RT) technology have increased tumor targeting and normal tissue sparing. Radiations at ultra-high dose rates required for FLASH-RT effects have sparked interest in potentially providing additional differential therapeutic benefits. We present a new experimental platform that is the first one to deliver petawatt laser-driven proton pulses of 2 MeV energy at 0.2 Hz repetition rate by means of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 62 publications
0
34
1
Order By: Relevance
“…The cell samples were located in air at 1.7 m downstream from the point of laser-target interaction. A portion of the TNSA ion beam was captured and transported downstream by an active plasma lens (APL) on a remote controlled hexapod [11,23]. The APL consisted of a 33 mm long capillary filled with argon gas at a pressure of 5 Torr inside the channel of 1 mm diameter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cell samples were located in air at 1.7 m downstream from the point of laser-target interaction. A portion of the TNSA ion beam was captured and transported downstream by an active plasma lens (APL) on a remote controlled hexapod [11,23]. The APL consisted of a 33 mm long capillary filled with argon gas at a pressure of 5 Torr inside the channel of 1 mm diameter.…”
Section: Methodsmentioning
confidence: 99%
“…At the current uncertainty associated with the model function for D(Q), (∆D/D) SSF could be lowered to ∼ 0.11 for total doses >2.5 Gy and even to < 0.1 for doses >10 Gy. It should be pointed out that the relative dose uncertainty resulting from lateral dose variations across the cell samples was 0.19 [11] and will also need to be reduced in the future to improve the overall irradiation precision, however, those efforts are beyond the scope of this paper.…”
Section: (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…With the biological mechanisms underlying the FLASH effect remaining largely unknown, research into the radiobiological effects of ultra-high dose rate proton irradiation has been hampered by limited access to conventional accelerators that are able to provide the required dose rates [97,98]. In a preliminary study at the 40 Joule BELLA petawatt laser proton beamline, it was demonstrated for the first time that LD protons delivered at ultra-high IDR can indeed induce the differential sparing of normal versus tumor cells in vitro for total doses ≥ 7 Gy [80]. In that study, normal and tumor prostate cells in 1 cm diameter cups were irradiation with LD protons of 2-8 MeV at an IDR of 10 7 Gy/s.…”
Section: Snowmass2021 Accelerator Frontier White Paper: Near Term App...mentioning
confidence: 99%